Effects of different heat–moisture treatments on the physicochemical properties of brown rice flour. Issue 12 (2nd December 2017) - Nakamura, Sumiko; Okumura, Hisako; Sugawara, Masayoshi; Noro, Wataru; Homma, Noriyuki; Ohtsubo, Ken'ichi
Abstract: We evaluated the effect of heat–moisture treatment (HMT) on the main chemical components, physical properties, and enzyme activities of two types of brown rice flour: high-amylose Koshinokaori and normal-quality Koshiibuki. Five different HMTs using brown rice (moisture content was 12.0%) were assessed: 0.1 MPa/120 °C for 5 or 10 min, 0.2 MPa/134 °C for 5 or 10 min and 0.3 MPa/144 °C for 10 min. HMT, decreased the α-amylase and lipase activities, and fat acidity, and slightly increased the dietary fiber and resistant starch levels. After 2 months' storage at 35 °C, rice samples that were treated with 0.2 MPa/134 °C or 0.3 MPa/144 °C for 10 min had a lower fat acidity than untreated samples, which would be useful for long-term storage and export of rice flour. And HMT exhibited inhibition of retrogradation in the pasting and physical properties, which is profitable to promote the qualities of the rice products. Graphical abstract: : There was no increase in the fat acidity of the samples treated with 0.3 MPa/10 min HMT during 2 months' storage at 35 °C.